2019
DOI: 10.1021/acsami.9b17141
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Ink with an Ultrawide Processing Window for Efficient and Scalable Perovskite Solar Cells in Ambient Air

Abstract: Perovskite solar cells (PSCs) have attracted tremendous attention because of their rapidly growing efficiency and low cost. However, the efficiency of scalably deposited PSCs, especially spray-coated devices, is still lagging far behind that of spin-coated devices because of the complicated crystallization of coated precursor ink. Here, we show a precursor ink with an ultrawide processing window (more than 40 min) for spray-coating by adjusting the precursor component, which benefits the scalable deposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…The next efficiency breakthrough came in late 2019, when Su et al reported devices with a PCE of 18.53% by optimizing the work of Uličná. 70 Here, the same solvent composition of NMP and DMF was used to spray cast devices, with the perovskite film subsequently dipped in a bath of diethyl ether antisolvent. This process is illustrated schematically in Figure 6 a; here, the film was deposited in a single spray pass before being submerged in an antisolvent bath and then subsequently annealed.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The next efficiency breakthrough came in late 2019, when Su et al reported devices with a PCE of 18.53% by optimizing the work of Uličná. 70 Here, the same solvent composition of NMP and DMF was used to spray cast devices, with the perovskite film subsequently dipped in a bath of diethyl ether antisolvent. This process is illustrated schematically in Figure 6 a; here, the film was deposited in a single spray pass before being submerged in an antisolvent bath and then subsequently annealed.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Such large devices demonstrated reverse scan PCE values of 15.07 and 13.21%, respectively, which are some of the highest values reported in the literature. 70 …”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the use of two-step deposition protocols 16 , continuous soaking of the substrate 17 , anti-solvent bath treatments 18 , the use of multiple spray-passes 19 , low vacuum treatments 20 , megasonic spray-coating 21 , and hot-air treatments 22 . Indeed, many groups can now reliably produce spray-coated PSCs with an average PCE in the mid-teens with the best devices reaching a reverse scan PCE of 18.5% and a stabilised PCE of 17.3% 23 . Furthermore spray deposition has been utilised to probe compositional space in mixed cation systems by controlling the flow of two inks delivered to the spray head prior to atomisation 24,25 .…”
mentioning
confidence: 99%
“…It is important to emphasize that the majority of papers on spray-coated PSCs rely on spin-coating to deposit the electron and hole transport layers that are used to extract charges from the active perovskite layer [16][17][18][19][20][21][22][23]26,27 . Ideally however, spray-coating should be used to deposit all solution processable layers within a PSC as this would replicate a practical manufacture process.…”
mentioning
confidence: 99%